Makna Sakral Ondel-ondel pada Generasi Betawi - Bianda Aulia; Nani Kurniasari (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
Ondel-ondel buskers are increasing day by day. Cempaka Putih Raya Street, is one of the busiest culinary areas in Central Jakarta. The location is a strategic area for buskers to lead their Ondel-ondels, not all visitors on Cempaka Putih Raya Street come from a Betawi cultural background or from Jakarta. This phenomenon is a concern for the researcher, especially in the shifting of the Ondel-ondel’s interpretation. This study aims to determine the shift in the interpretation of Ondel-ondel’s sacrality in the Original Betawi and Mixed Betawi generation. The researcher conducted a semi-structured interview with six informants, consisting of Original Betawi people and Mixed Betawi people. This type of research is comparative descriptive, the researcher made comparations from the answers of four informants. The result show that there was a shift in Ondel-ondel’s sacred image obtained from testing the perception of informants. The results show that Ondel-ondel’s meaning has experienced a modification in interpretation. The modification that occurred is the shift from sacrality into commodity due to the Ondel-ondel busker phenomenon.